Flora de acanthaceae juss. e verbenaceae j.st.-HIL. (LAMIALES) no parque nacional do Iguaçu, Paraná, Brasil. - Hammes, Janaine Kunrath (2017)
The Iguaçu National Park (ParNa Iguaçu) is one of the few remnants of the western Paraná, composed by semideciduous forest and Araucaria forest. The aim of this work was to perform a floristic survey of Acanthaceae and Verbenaceae of ParNa Iguaçu. Collections were carried out monthly from August 2015 to July 2016, the individuals were deposited in the UNOP herbarium and the specimens present in the herbaria EVB, HCF, MBM and UNOP, as well as in the virtual herbaria Reflora and SpciesLink were analyzed. We recorded 20 species, 12 Acanthaceae and eight Verbenaceae, distributed in six genera each; 19 are new records for ParNa Iguaçu. Lantana fucata and Bouchea fluminensis (Verbenaceae) are new records for Paraná and Streblacanthus dubiosus (Acanthaceae), in Paraná, it is known only to the ParNa Iguaçu.